BUILDING LOAD IN THE PROCESS OF PHYSICAL EDUCATION OF STUDENTS OF SPECIAL EDUCATIONAL DEPARTMENT (Education in the 21st Century, 2023)
This article reveals the basic factors, signs and indicators of tiredness to be obligatory considered in the process of organizing and conducting physical activities with students with different types of visual impairment. As the different forms and degrees of visual impairment, psychophysical peculiarities of development, lack of development of motor skills and orientations in space of those students determine the importance and necessity of using protective means and mobilizing stand-by resources at gym classes.It has been established, that the deep and partial visual impairment significantly impede the motor possibilities of students, their orientation in macro and micro-spaces, understanding the teaching material of physical education program and participating in the physical and sport activities. Therefore, in order to prevent injuries and further visual impairments in students during physical activities in school, university and gyms, we have to take into account the gender, form and degree of visual impairment, the availability of concomitant diseases, secondary developmental deviations, the level of physical preparedness of students and many other factors.This will serve as the basis for health strengthening in students with different types of visual impairment. The abovementioned points define the relevant, theoretical and practical significance of the present research theme․
Keywords: students; special educational department; upbringing; physical activity; forms and degree of developmental disorders; load regulation